Plan exportador para la empresa A&A Marroquinería de Colombia de bolsos en cuero de bovino sin depilar. (2013)
Colombian exports are a trade, pointing to the country's economic development. Which is why the Colombian government is currently encouraging the export orientation of the large, medium and small businesses through various training programs offered by institutions such as Proexport, Camara de Comercio and Sena, as well as the recent signing of various treaties free trade agreement (FTA), with the most powerful and globalized economies of the world, including (United States of America, European Union and South Korea), among others. In order to facilitate insertion into international markets and participate in global trade dynamics. Therefore this research wants to establish the feasibility of exporting bovine leather handbags without depilate towards the U.S. market, by the company A&A MARROQUINERIA of COLOMBIA. Besides proposing a target market where variables stand out as the status of the product in the market, supply and demand, potential consumer characteristics, macroeconomic and microeconomic factors in general and local consumption of the product. Also studied the economic performance and production aspects of leather in both countries, especially the bags in leather product that was chosen to present important features for quality and design, with the premise that the company A&A MARROQUINERIA is a company with 4 years of experience in the trade which is to design, develop and market items leather goods in Caldas and Quindío Departments, having high acceptance of products and expectations of opening new international markets